EXPLICIT AND IMPLICIT MEANINGS IN ELONG „BUANG TASSANRA MUA‟ - Harun, Sudarmin (Universitas Hasanuddin, 2014)
This writing aims to transfer Buginese Elong ‗song‘ into English and to reveal the meanings thatcontained in buginese traditional song entitles Buang Tassanra Mua ‗Fall down but Safe‘. Thissong is very interesting to be analyzed and to reveal deeply either its explicit or implicitmeanings because it has many meanings that must be known not only buginese but also the otherethnics in Indonesia and abroad, even also all generations outside or at schools and university.By revealing the meanings explicitly or implicitly of the song, a person could aware that theancestor‘s advices are very important to implement in his/her daily life. All generations shouldknow, keep, and put them in their mind in order to become a guidance to do good things and toavoid to do bad actions such as breaking the buginese ade ‗customs‘, bicara ‗laws‘, rapang‗ruls‘ and wari‟ ‗etics‘.The objective of Elong ‗song‘ is as not only a medium of entertainment solely but it could alsobe a medium of conveying some advices and it could be a medium of teaching language andlingua franca as well as teaching literature. Lectures and teachers have a must to transfer thebuginese songs into English with the goal the foreigners could read and know the buginese locallanguage and literature, especially buginese pappaseng ‗local wisdom‘ that contained in thissong – buginese language and literature.Key words: Buginese Elong, language, and literature.